A oscuras - Jules, Jacqueline, 1956-; Smith, Kim, 1986- (North Mankato, Minnesota : Picture Window Books, a Capstone imprint, 2018)
When a storm causes a neighborhood blackout, Sofia and her father come up with a plan for the perfect family night without electricity.
Accelerated Reader AR
In Spanish.
Keywords: Hispanic American families -- Juvenile fiction; Electric power failures -- Juvenile fiction; Spanish language materials; Fallas de energia elcetrica -- Novela juvenil